D-dimer may aid in the diagnosis of pediatric musculoskeletal infections: a prospective study. Issue 1 (January 2023) - Topak, Duran; Nazik, Selçuk; Seyithanoglu, Muhammed; Temiz, Ahmet; Mutlu, Halil; Özdemir, Mustafa Abdullah; Doğar, Fatih; Bilal, Ökkeş
Abstract : Musculoskeletal infections, including septic arthritis, osteomyelitis, and soft tissue infections, are critical morbidity factors for children and adolescents. This study investigated the role of D-dimer levels for diagnosing childhood musculoskeletal infections. This single-center prospective study was initiated in April 2020 following approval from the local ethics committee. The study included 54 children, divided into the infection group ( n = 21), comprising patients who underwent surgical treatment for childhood musculoskeletal infections and had macroscopically visible purulent discharge during surgery, and the control group ( n = 33), comprising healthy children. In the infection group, the mean values of erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), plasma D-dimer, and white blood cell (WBC) were 39.42 ± 27.00 mm/h, 101.50 ± 76.90 mg/l, 2.34 ± 2.59 mg/l, and 15.55 ± 6.86 × 10 9 /l, respectively. On comparison, the infection group showed higher levels of WBC, CRP, ESR, D-dimer, and neutrophil-to-lymphocyte ratio than the control group. When the D-dimer cutoff value of 0.43 mg/l was taken, it was observed that it had 95.2% sensitivity and 81.8% specificity. The area under curve (AUC) of the above-mentioned parameters calculated via receiver operating characteristic curves showed CRP levels as the optimum predictor of childhood musculoskeletal infections, followed by the ESR, plasma D-dimer, and WBC levels in descending order (AUC: 0.999, 0.997, 0.986, and 0.935, respectively). D-dimer is another test, which in combination with other conventional established tests (CRP and ESR) can be helpful in diagnosis of pediatric infection. We recommend the addition of D-Dimer to ESR, CRP, and WBC as a first-line investigation in cases with suspected pediatric musculoskeletal infections.